The Role of One Health Framework to Neglected Tropical Diseases in South East Asia: A Literature Review - Tedjaprasadja, Leonardo (Journal of Diverse Medical Research: Medicosphere, 2025)
Neglected tropical diseases (NTDs) remain a significant public health challenge in Southeast Asia, disproportionately affecting marginalized communities and exacerbating cycles of poverty and poor health. These diseases often arise at the interface of human, animal, and environmental health, necessitating a transdisciplinary approach. The One Health framework, which integrates human, animal, and environmental health strategies, offers a holistic and sustainable solution to combat NTDs in the region. This article explores the application of One Health in addressing NTDs such as dengue, leptospirosis, schistosomiasis, and rabies across Southeast Asia. It highlights current regional initiatives, identifies challenges including fragmented surveillance systems and limited intersectoral coordination and underscores the importance of cross-border collaboration, community engagement, and policy integration. Emphasizing the need for sustained investment and capacity building, the article advocates for strengthening One Health systems as a pathway toward effective NTD control and elimination in Southeast Asia.